KAJIAN HUKUM EKONOMI ISLAM TERHADAP PRAKTIK JUAL BELI CRYPTOCURRENCY DI INDONESIA - Ali Hardana; Hasir Budiman Ritonga (Yurisprudentia: Jurnal Hukum Ekonomi, 2025)
The development of digital technology has brought about various innovations in the financial system, one of which is cryptocurrency as a means of exchange and investment instrument. However, the legality and permissibility of cryptocurrency trading remain controversial, especially from the perspective of Islamic economic law. This study aims to examine the legal status of cryptocurrency trading in light of Islamic economic principles and assess its practice in Indonesia based on core sharia principles such as justice, transparency, and avoidance of gharar (uncertainty) and maisir (speculation). This research employs a qualitative normative approach through library research and in-depth interviews with Islamic economic practitioners, along with analysis of relevant fatwas, including those issued by the Indonesian Ulema Council (DSN-MUI) and opinions of contemporary scholars. The results show that cryptocurrency trading contains a high level of speculation and does not fully comply with sharia principles, particularly regarding price stability and transaction object clarity. Nevertheless, there is a diversity of scholarly opinion; some scholars prohibit its use due to elements of gharar and maisir, while others permit it under specific conditions. In conclusion, cryptocurrency trading practices in Indonesia still require clearer guidance from an Islamic legal perspective. There is a need for more specific regulations, fatwas, and public education to ensure that digital asset transactions align with the principles of Islamic economic law.